Efecto de la fermentación sumergida en niveles de taza de dos variedades de café especial del Perú. - Salas-Pastor, Y. (2023)
The consumption of special coffees has been gradually increasing and affecting in their prices, not only for the domestic market; but also in the foreign market. The different methods of coffee processing will directly influence the cup quality. Taking this into consideration, this study has as an objective evaluated the cup quality of two varieties of Peruvian special coffee subjected to submerged fermentation. This research was done in a Central Composite Rotational Design (CCRD) containing four factorial experiments, four axial experiments and three core repeats. It was evaluated the cup quality of two varieties of coffee subjected to different temperatures (8, 9, 12, 15 and 16 °C) and fermentation times (48, 62, 96,130 and 144) submerged in relation 70:30; having as a result that the geisha variety presents greater values than 86 points, continued by caturra variety with less values than 85.75 points, with temperatures above 16° C and times between 90 and 100 hours.